2018
DOI: 10.1002/cnma.201700384
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Immobilized on Graphene‐Oxide‐Containing Palladium Metal Ions as an Efficient Catalyst for the Alkoxy, Amino, and Phenoxy Carbonylation Reactions

Abstract: The Immobilization of homogeneous metal catalysts onto the solid surface is an important challenge in the field of catalysis because these types of catalysts provide the homogeneous nature as well as reusability of catalysts. In this report, novel Palladium ion containing ionic liquid immobilized onto graphene oxide (Pd@GOIL) and characterized using various analytical techniques like FT‐IR, XPS, TGA, SEM, TEM, BET and EXAFS analysis. This synthesized material acts as a highly efficient catalyst for the alkoxyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…XPS analysis of the spent catalyst revealed that the degree of reduction increased up to 57 %. Material 137 was also used as support of Pd(II) species by ion exchange with PdCl 2 giving rise to hybrid 139 that was applied as efficient catalyst for alkoxy, amino, and phenoxy carbonylation reactions (Scheme ) . Carbonylation reactions were tested with a very broad substrate scope and it was possible to synthesize esters and amides under mild reaction conditions.…”
Section: Graphene‐ Graphene Oxide‐ and Reduced Graphene Oxide‐based mentioning
confidence: 99%
“…XPS analysis of the spent catalyst revealed that the degree of reduction increased up to 57 %. Material 137 was also used as support of Pd(II) species by ion exchange with PdCl 2 giving rise to hybrid 139 that was applied as efficient catalyst for alkoxy, amino, and phenoxy carbonylation reactions (Scheme ) . Carbonylation reactions were tested with a very broad substrate scope and it was possible to synthesize esters and amides under mild reaction conditions.…”
Section: Graphene‐ Graphene Oxide‐ and Reduced Graphene Oxide‐based mentioning
confidence: 99%
“…The biaryl ketones are very important structural scaffolds found in a wide variety of the molecules. Among the various methods reported for the synthesis of biaryl ketones, carbonylative Suzuki–Miyaura coupling by using carbon monoxide (CO) as the C1 source is considered as the most prominent method because of the wide functional group tolerance. , Number of homogeneous and heterogeneous palladium-based catalysts are well-documented in literature. , By considering the high activity of synthesized Pd@APGO catalyst for the synthesis of biaryls, we applied for the synthesis of biaryl ketones by using CO, aryl halides, and aryl boronic acids. Initially, CO (2 bar), aryl iodide c (1 mmol), phenylboronic acid b (1.2 mmol), Pd@APGO (5 mg), anisole (10 mL), and K 2 CO 3 (1.5 mmol) were utilized for the synthesis of biaryl ketones 16 at 80 °C.…”
Section: Resultsmentioning
confidence: 99%
“…40,41 Number of homogeneous and heterogeneous palladium-based catalysts are well-documented in literature. 42,43 By considering the high activity of synthesized Pd@APGO catalyst for the synthesis of biaryls, we applied for the synthesis of biaryl ketones by using CO, aryl halides, and aryl boronic acids. Initially, CO (2 bar), aryl iodide c (1 mmol), phenylboronic acid b (1.2 mmol), Pd@ APGO (5 mg), anisole (10 mL), and K 2 CO 3 (1.5 mmol) were utilized for the synthesis of biaryl ketones 16 at 80 °C.…”
Section: Table 2 Substrate Study For the Synthesis Of Biaryls Abmentioning
confidence: 99%
“…Protic ILs have been used as acid catalysts to hydrolyze and dehydrate carbohydrates derived from biomass into renewable chemical platforms such as 5-hydroxymethylfurfural (HMF), levulinic acid (LA), and furfural (FUR) [ 14 ]. There are various means of loading ILs onto different carrier materials, such as magnetic nanoparticles [ 15 , 16 ], graphene [ 17 ], molecular sieves [ 17 ], metal skeletons, etc. Various types of supported functional ILs (SFILs) have been prepared, which, in addition to providing a good ionic environment, form strong interactions with the reaction substrate, resulting in better catalytic effects.…”
Section: Application Of Ilsmentioning
confidence: 99%